2005
DOI: 10.1038/sj.onc.1208447
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of plasma cell dyscrasias reveals molecular patterns associated with distinct IGH translocations in multiple myeloma

Abstract: Multiple myeloma (MM) is the most common form of plasma cell dyscrasia, characterized by a marked heterogeneity of genetic lesions and clinical course. It may develop from a premalignant condition (monoclonal gammopathy of undetermined significance, MGUS) or progress from intramedullary to extramedullary forms (plasma cell leukemia, PCL). To provide insights into the molecular characterization of plasma cell dyscrasias and to investigate the contribution of specific genetic lesions to the biological and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
111
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 57 publications
2
111
0
1
Order By: Relevance
“…Using DNA microarrays, we and others have shown that genes belonging to the MAGE and SSX families and NY-ESO-1 were aberrantly expressed in a certain percentage of primary MMC (29,30). The expression of NY-ESO-1 has been correlated with a poor prognosis and its frequency is increased in patients displaying genetic abnormalities determined by conventional cytogenetic analyses (31).…”
Section: Ultiple Myeloma (Mm) 3 Is a B Cell Neoplasia Charac-mentioning
confidence: 95%
“…Using DNA microarrays, we and others have shown that genes belonging to the MAGE and SSX families and NY-ESO-1 were aberrantly expressed in a certain percentage of primary MMC (29,30). The expression of NY-ESO-1 has been correlated with a poor prognosis and its frequency is increased in patients displaying genetic abnormalities determined by conventional cytogenetic analyses (31).…”
Section: Ultiple Myeloma (Mm) 3 Is a B Cell Neoplasia Charac-mentioning
confidence: 95%
“…The RNA integrity was verified by means of an Agilent Technologies 2100 Bioanalyzer. The biotin-labeled cRNA was synthesized as previously described (49). In accordance with the Affymetrix protocols, 15 μg of fragmented cRNA was hybridized on GeneChip Human Genome U133A Arrays (Affymetrix) after quality checking on GeneChip Test3 Arrays (Affymetrix).…”
Section: Methodsmentioning
confidence: 99%
“…Unsupervised analyses were applied to a subset of genes whose average change in expression levels varied at least 2-fold from the mean across the whole panel. Hierarchical agglomerative clustering and dendrogram generation were used to search for natural groupings in the profiles using DNA-Chip Analyzer (dChip) software (25); in order to perform the clustering of the selected probe lists, Pearson's correlation coefficient and average linkage were used as distance and linkage methods, respectively (49,50). The supervised gene expression analyses were performed using the Gene@Work software platform as previously described (49).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations